Spurring Growth in Lagging Regions in Slovak Republic - Demmou, Lilas (OECD Economics Department Working Papers, 2015)
Regional inequality in Slovakia is among the highest in the OECD and is increasing. The main reason for regional disparity is the combination of low economic growth and job creation in the eastern and central part of the country and insufficient labour mobility to the west, in particular by low-skilled workers. As a result, jobs shortage and lack of technological capacities in the central and eastern regions persist alongside skills shortages in the Bratislava regions. Boosting convergence requires a multi-pronged approach involving innovation, labour market and educational policies. Completing the transport infrastructure network in Slovakia will be both important for removing expansion bottlenecks in the Bratislava region and reducing obstacles for job creation in the central and eastern regions